Student led outreach workshops to promote Basic Life Support - Sadia Ahsin; Madiha Imran; Ammad Fahim; Liaquat Hussain (Journal of the Pakistan Medical Association, 2021)
Objectives: Primary aim of this project was to provide BLS training to staff, students and faculty of higher educational institutes of Rawalpindi and Islamabad (twin cities in Punjab, Pakistan) through pre-trained medical students. Secondary aim of the study project was to qualitatively record the impact of community training on student facilitators who conducted BLS workshops, through semi structured interviews. Methods: A mixed method Quasi experimental study was carried out at Foundation University Islamabad in collaboration with Higher Education Commission of Pakistan from 2015 to 2018. BLS trained 120 volunteer medical students were divided in 20 teams to visit and provide hands-on training to 20 educational institutes with 45-50 participants each. These participants completed pre and post training questionnaires, whereas, student trainers went through post training semi structured interviews. Quantitative analysis of participants pre and post training responses was done using SPSS 21. Qualitative assessment of impact on students was done through constant comparative analysis of transcripts. Results: A total of 675 participants including students, faculty and staff received hands on BLS training. Questionnaire based analysis of participants BLS knowledge showed >99% improvement (p < 0.001) after training. Main recurring themes identified in transcribed student interviews were, opportunity to improve self-confidence and technical skill. Conclusion: Hands on training sessions conducted by pre-trained medical students not only resulted in improvement in BLS knowledge of participants at various educational institutes but also had substantial impact on student trainers self-confidence and technique. Continuous...